Efeitos do Treinamento Intervalado de Alta Intensidade – HIIT protocolo Tabata Sobre a Composição Corporal e Aptidão Física de Jogadores de Futsal - MAGALHÃES, Márcio Tavares (2023)
Objective: Check the effects of high-intensity interval training HIIT Tabata protocol on body and physical composition of futsal players. Materials and methods: The sample consisted of 61 male futsal players, aged between 15 and 35 years, divided into three categories under-17, under-20 and adult with control group (n=16) and intervention (n=45). Individual futsal players for at least 6 months, attending team training and aged between 15 and 35 years were included in the survey. Subjects followed the HIIT Tabata protocol (20:10) for 4 minutes three times a week for 12 weeks. Statistical analysis: Mean and standard deviation descriptive data were used, as well as the Shapiro-Wilk test was used for data normality, mixed factorial ANOVA was used for inferential statistics. Results: The results show that body weight had a significant reduction in both categories, under-20 (p<0.001) and adults (p<0.001) in the intervention group. The percentage of fat decreased significantly in both categories, under-20 (p<0.001) and adults (p<0.021) in the intervention group. Lean body mass was reduced in both categories, under 20 (p<0.001) and adult (p=0.06) in the intervention group. Fat mass attenuated by 2.05 kg for sub-20 (p<0.001) and 1.44 kg in the adult category of the intervention group (p=0.06). There were significant gains in VO2max for individuals in the under 20 (p=0.00) and adult (p=0.05) categories of the intervention group, there were no significant results in VO2max for both categories in the control group. Vertical jump ability significantly improved in both categories of the intervention group, under-20 (p<0.001) and adults (p<0.001). Upper limb strength improved significantly in the under-20 category (p=0.00) but was not effective in the adult category (p=0.20) in the intervention group. Abdominal strength had an increase in the average number of repetitions achieved in the post-intervention compared to pre-intervention data in both categories, under-20 (p<0.001) and adults (p=0.01) in the intervention group. Conclusion: The results obtained in the present study indicate that the 36 sessions of high intensity interval training - HIIT Tabata, were effective in improving the body composition and physical capacity of futsal players throughout their training.